(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This paper looks at the development of our knowledge of the Celtiberian lexicon since the year 2000. Newly found lexemes and new readings contribute to an expanded picture of word formation and typically Celtic words.